2022
DOI: 10.1038/s41598-022-05873-w
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory responses of Trissolcus mitsukurii to plants attacked by target and non-target stink bugs suggest low risk for biological control

Abstract: In crop systems, successful management of invasive insect herbivores can be achieved through the introduction of exotic biocontrol agents, parasitoids or predators, having a coevolutionary history with the pest. To avert threats to local biodiversity, recent legislations require a risk assessment for the organism to be released. Evaluation of its ability to exploit, for host location, odours associated with target and non-target species is crucial for a better definition of its ecological host range. Using Y-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…This detail could presume the existence of some sort of co-evolutionary or adaptation process. A recent survey on the olfactory response of T. mitsukurii confirms this inclination for N. viridula [ 42 ]. Indeed, the parasitoid manifested an interest in the arm containing a plant contaminated by N. viridula , which was previously exposed to individuals for feeding and oviposition [ 42 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This detail could presume the existence of some sort of co-evolutionary or adaptation process. A recent survey on the olfactory response of T. mitsukurii confirms this inclination for N. viridula [ 42 ]. Indeed, the parasitoid manifested an interest in the arm containing a plant contaminated by N. viridula , which was previously exposed to individuals for feeding and oviposition [ 42 ].…”
Section: Discussionmentioning
confidence: 67%
“…Conversely, BMSB cues elicited a modification in the kinetic reaction with a reduced intensity. The aforementioned interest was confirmed in olfactory investigation [ 42 ], while discordant results were highlighted in the physiological host range [ 43 ]. Additional analyses are needed to prove this preference.…”
Section: Discussionmentioning
confidence: 99%
“…Bertoldi et al (2019) found a strong preference in T. japonicus for olfactory cues of its putative coevolved BMSB host, even when it emerged from other species (Boyle et al 2020). In northern Italy, adventive populations of T. mitsukurii also display a strong preference for BMSB (Rondoni et al 2022).…”
Section: Biology Of the Egg Parasitoidsmentioning
confidence: 94%
“…In contrast, T. mitsukurii showed significantly lower emergence percentages in egg masses treated with Dentamet ® , despite the high proportion of parasitized eggs (> 81%) for all treatments. Since the exposure to H. halys egg masses in the absence of the host plant was reported to be inefficient in attracting this wasp (Rondoni et al 2022), the odour blend emitted after treatment with Dentamet ® may further impair the wasp recognition of the host eggs, at least in our experimental conditions, where no plant was offered to the wasp. The elimination of P. carbekii may interfere with the attraction exerted by some symbiont-derived volatiles; the interference with attraction for volatiles may be exacerbated by the general non-preference of T. mitsukurii for wet eggs, as evidenced by the untreated vs treated with water paired choice test.…”
Section: Discussionmentioning
confidence: 91%